2012
DOI: 10.1097/sa.0b013e318254dc70
|View full text |Cite
|
Sign up to set email alerts
|

Identical De Novo Mutation in the Type 1 Ryanodine Receptor Gene Associated With Fatal, Stress-Induced Malignant Hyperthermia in Two Unrelated Families

Abstract: BACKGROUND-Mutations in the type I ryanodine receptor gene (RYR1) result in malignant hyperthermia, a pharmacogenetic disorder typically triggered by administration of anesthetics. However, cases of sudden death during exertion, heat challenge, and febrile illness in the absence of triggering drugs have been reported. The underlying causes of such drug-free fatal "awake" episodes are unknown. METHODS-De novo R3983C variant in RYR1 was identified in two unrelated children that experienced fatal, nonanesthetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Family counselling is vital to identify potentially MH-susceptible relatives [1] We performed a systematic literature review (including the patients in the studies mentioned above), based on a Pubmed search with "RYR1" and "rhabdomyolysis". This resulted in identification of several case report and small series [1,8,[21][22][23][24][25][26], and two review article [27,28] Subsequently, we also included cases from references of these articles [20,26,[29][30][31][32][33][34] and added our recent letter by Snoeck et al [35]. Finally, we added two patients from our paper on the spectrum of RYR1 related myopathies by Snoeck et al who were not included in any other publication (patients 14 and 52 [1]).…”
Section: Ryr1-related (Exertional) Rhabdomyolysis ((E)rm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Family counselling is vital to identify potentially MH-susceptible relatives [1] We performed a systematic literature review (including the patients in the studies mentioned above), based on a Pubmed search with "RYR1" and "rhabdomyolysis". This resulted in identification of several case report and small series [1,8,[21][22][23][24][25][26], and two review article [27,28] Subsequently, we also included cases from references of these articles [20,26,[29][30][31][32][33][34] and added our recent letter by Snoeck et al [35]. Finally, we added two patients from our paper on the spectrum of RYR1 related myopathies by Snoeck et al who were not included in any other publication (patients 14 and 52 [1]).…”
Section: Ryr1-related (Exertional) Rhabdomyolysis ((E)rm)mentioning
confidence: 99%
“…Groom et al reported a de novo RYR1 variant (R3983C) in two unrelated children who experienced fatal, non-anesthetic MH episodes associated with febrile illness and heat stress. One of those children had numerous episodes of leg cramping, tachycardia, tachypnea and increased creatinine kinase years before the fatal episode [29].…”
Section: Box 2: Ryr1-related Exertional Rhabdomyolysis (Erm) In a 16-mentioning
confidence: 99%
“…We are happy to see that our editorial 1 prompts discussion, even though the points raised by Larach et al result mainly from the removal of the designated statement of the global context of the editorial. Three points of criticism were made: (1) the interpretation of the in vitro contracture test result of the boy (Groom et al…”
mentioning
confidence: 99%
“…Loubser and Sheinbaum purport in their letter that "Based on the lessons learned from cerebrospinal fluid drainage, and in the interests of patient safety, we should view neurophysiologic monitoring during TAAA [thoracoabdominal aortic aneurysm] surgery not as an obscure modality as Vaughn et al impugn, 1 but as a standard-of-care." Although it is fair to acknowledge that some centers have successfully adopted these techniques in the interests of patient safety, we disagree that these techniques should be considered "standard of care" (which has major medicallegal connotations).…”
mentioning
confidence: 99%
“…An association between RYR1 variants and exertional-or heat-induced rhabdomyolysis and sudden death has been reported [10][11][12][13]. The correlation between MH and EHS is also supported by evidence collected in animal models: (a) in porcine stress syndrome (PSS), swine carrying a point mutation in RYR1 trigger MH episodes in response to halothane administration but also following exposure to either heat or emotional/ physical stress [14,15]; (b) knock-in mice carrying gainof-function point mutations in RYR1 linked to MH in humans exhibit heat-and anesthetic-induced MH episodes [16,17].…”
Section: Introductionmentioning
confidence: 99%